Fungal Pigments 2021 - Dufossé, Laurent (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
New edition of the reprint Fungal pigments: Chapters titles: PART 1. Investigation on various chemical classes of fungal pigments: Genomic Analysis and Assessment of Melanin Synthesis in Amorphotheca resinae by Jeong-Joo Oh et al.; Fungal Melanins and Applications in Healthcare, Bioremediation and Industry by Ellie Rose Mattoon et al.; Recent Findings in Azaphilone Pigments by Lúcia P. S. Pimenta et al.; Characterization of a Biofilm Bioreactor Designed for the Single-Step Production of Aerial Conidia and Oosporein by Beauveria bassiana PQ2 by Héctor Raziel Lara-Juache et al.; PART 2. Molecular characterization: Molecular Characterization of Fungal Pigments by Miriam S. Valenzuela-Gloria et al.; PART 3. Biological properties: Seven New Cytotoxic and Antimicrobial Xanthoquinodins from Jugulospora vestita by Lulu Shao et al.; PART 4. Toxicity assessment and safety evaluation of fungal pigments: Safety Evaluation of Fungal Pigments for Food Applications by Rajendran Poorniammal et al.; Preliminary Examination of the Toxicity of Spalting Fungal Pigments: A Comparison between Extraction Methods by Badria H. Almurshidi et al.; PART 5. Use of by-products or waste for industrial production of fungal pigments: Production of Bio-Based Pigments from Food Processing Industry By-Products Using Aspergillus carbonarius by Ezgi Bezirhan Arikan et al.; PART 6. Prospective aspects and brainstorming: Does Structural Color Exist in True Fungi? by Juliet Brodie et al.; Fungal Biomarkers Stability in Mars Regolith Analogues after Simulated Space and Mars-like Conditions by Alessia Cassaro et al.